Dynamics with coquaternions - Falcão, M. I. (2018)
In this note, we give a first insight into the world of coquaternions, reflecting the recent interests of the authors. In particular, we recall some results on the zeros of coquaternionic polynomials and discuss several aspects of the dynamics of one family of quadratic maps on coquaternions. The nature of the algebra under consideration leads to results which can be considered as even richer and more interesting than the ones obtained in the complex or quaternionic cases.